Paradigm of Science and Religion Interconnection in Language Study: The Case of the Origin of Human Language - Albert, Albert; Irwandi, Irwandi; Aprison, Wedra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
Language is the most important characteristic that distinguishes humans from other animal species. Human language seems to be a unique phenomenon and has long been the object of study. The ability of humans to communicate with one another in intelligent, symbolic, often abstract speech and writing is considered a complete mystery to evolutionists. In fact, they cannot explain how the language originated. Linguists then put forward various theories about the origin of language. Unfortunately, there are also insufficient theories to explain not only how human speech came about, but also why there are so many different languages ​​that have developed in the world. In the interconnection paradigm of science-religion, this can be connected with the exploration of the verses of the Qur'an that discuss human language. As a permanent miracle revealed by Allah to the Prophet Muhammad. The Qur'an in depth talks about human linguistic communication. This paper discusses the theory of the origin of human language based on the perspective of the Qur'an and science. The evidence conclusively implies that God created humans with unique abilities in spoken and written communication, and even taught them to speak.